Wit issie 'n colour nie (it is a "sermon"!)?: After preaching, faith formation, and whiteness in contemporary South Africa - Laubscher, Martin (Stellenbosch theological journal, 2023)
There is a growing need to critically engage the three loaded key concepts in our title - preaching, faith formation, and whiteness - within the contemporary South African context. In doing so, I propose a reflective reading on the following three primary texts, namely Nathan Trantraal's Wit issie 'n colour nie (2018), Johan Cilliers' God for us? An analysis and assessment of Dutch Reformed preaching during the apartheid years (2006 [1994]), and Willie James Jennings' After whiteness - A theological education in belonging (2020). The background for this discussion is to recognise the "(white) elephant in the room", confess that it is not simply a mere matter of "(just) white noise", or telling "secret little (white) lies", and examine how whiteness in our sermons may be transformed and more transformative of more colourful and imaginative Christian witness.ess.